Electrospun carbon/iron nanofibers: The catalytic effects of iron and application in Cr(VI) removal. (30th September 2020) - Lu, Yang; Liu, Zhongqi; You, Seung Woon; McLoughlin, Lauren; Bridgers, Bailey; Hayes, Seth; Wang, Xifan; Wang, Ruigang; Guo, Zhanhu; Wujcik, Evan K.
Abstract: Electrospun polyacrylonitrile/iron nitrate (PAN/Fe(NO3 )3 ) nanofibers were prepared, and used as precursor nanofibers for production of carbon/iron nanofibers via the carbonization process. The catalytic effects of metallic iron on morphologies, chemical structures, graphitic carbon growth, and thermal behavior during and after the carbonization process were carefully investigated. The existence of iron nitrate can increase the fiber size and convert the non-woven morphology into self-aligned assembly. The presence of catalytic iron facilitates the stabilization and the carbonization of PAN fibers resulting in an increased carbon yield, along with more ordered and larger graphitic crystallites. The developed carbon/iron nanofibers can be used as an ultra-effective nanoadsorbent to remove the toxic Cr(VI) in water, as one of the potential applications. The nanoadsorbent shows a fast and powerful performance in Cr(VI) removal through reduction and adsorption (maximum removal capacity of 445.3 mg/g). The α-Fe nanoparticles on carbon nanofiber surface is first oxidized to rapidly reduce the mobile Cr(VI) into the static Cr(III). Subsequently, the diffusion controlled redox reactions between the iron inside of carbon matrix and the Cr(VI) achieve a sustained continuous Cr(VI) removal for 60 days. Furthermore, this versatile material is magnetic making separation and recycle easy to perform. Graphical abstract: Image 1